Co-modulation of clinical courses of hypertension and depression in public health facilities in Ethiopia: A six-month follow-up study protocol - Anemaw Asrat; Getnet Mitike; Fentie Ambaw (PLoS ONE, 2026)
Background The co-occurrence of hypertension and depression is increasing both in magnitude and complexity, negatively impacting treatment outcomes of both conditions. Given that both conditions are chronic, the impact of each condition over time on the other needs to be well understood. This project aims to examine how each condition affects the course and outcome of the other over a six-month follow-up period. Methods Four hundred eighty-five adults with newly diagnosed hypertension will be screened for depression using the nine-item Patient Health Questionnaire (PHQ-9) at the time of diagnosis. We will employ a prospective cohort study design, with depression serving as the exposure variable. At baseline, blood pressure, depression level, co-morbid illness, perceived social support, substance use, pain level, health-related quality of life, and disability will be measured. At three and six months, blood pressure, depression level, health-related quality of life, and disability measurements will be repeated. The prevalence of depression will be determined at baseline, and the factors associated with it will be examined using Poisson regression with a robust variance estimator. The incidence of depression will be calculated at 3 months and 6 months. The effect size of the change from baseline to endpoint will be measured using Cohen’s d. To identify the predictors of change in PHQ-9 scores over time, multilevel mixed-effects linear regression will be employed. Blood pressure control at three and six months will be evaluated, and the impact of baseline depression on blood pressure control will be analysed. P-values less than 0.05 will be considered statistically significant. Ethics The Institutional Review Board of the College of Medicine and Health Sciences, Bahir Dar University, has approved the study. Anticipated impact The findings will contribute to the scarce body of knowledge about long-term interaction between hypertension and depression, particularly on the impact of unmanaged depression on hypertension control, and the incidence of depression in hypertension patients. Findings on the course of depression will help clinicians to decide on the dilemma of treating it or expecting spontaneous recovery with the effective management of hypertension.